A mixed-method approach for the assessment of local community perception towards wind farms. (June 2019) - Ferreira, Paula; Lima, Fátima; Ribeiro, Fernando; Vieira, Filipa
Abstract: The implementation of wind power projects can have significant impacts on local communities. If on one hand the project can bring important economic benefits, on the other hand it can represent a source of conflicts and discontentment. This paper aims to revisit this topic, addressing impacts and their perceptions from the local community point of view. A mixed method approach was proposed and implemented in a Portuguese region (municipality) used as case study. Semi-structured interviews directed towards local stakeholders were conducted to evaluate the acceptance of these wind power projects and the perceived impacts. The qualitative study was subsequently complemented and validated by a quantitative approach, through a questionnaire targeting local population. In general, the collected opinions seem mainly driven by the perceived socio-economic benefits resulting from wind farm deployment, with generally positive attitude towards wind farms. Identified local positive impacts include "community funds", "benefits in kind" and "indirect local employment". The key role of benefit sharing mechanisms on ensuring public acceptance and effective local development is confirmed.